Các nhân tố ảnh hưởng đến việc thực hiện dự án giáo dục STEAM ở trường mầm non - Phạm, Quang Thuận; Phan, Thị Kim Liên; Cao, Thị Hồng Nhung; Bùi, Văn Hồng (Tạp chí Giáo dục, 2024)
STEAM education helps preschool children develop knowledge and skills to be ready to integrate into the 21st century. In Vietnam, STEAM education is an issue of interest to many researchers. Studies have shown that there are many factors affecting the implementation of STEAM education projects in preschools. However, no study has shown the importance of each factor. Based on the partial use of the model and questionnaire in the study by Bui Thi Lam et al. (2023), the article conducted a survey of 519 preschool teachers who had been trained in STEAM education courses. The results showed that two factors: preschool teachers’ capacity to implement STEAM education projects and school policies and leadership in implementing STEAM education projects play an important role in the effectiveness of STEAM education in preschools. The study recommends that preschool education students and preschool teachers need to be trained in STEAM education to be able to effectively implement STEAM education projects in preschools.